Calories recommendation mobile application for diabetic using rule based expert system / Nurul Afifah Mior Ghazali - Mior Ghazali, Nurul Afifah (2016)
Diabetes is one of the diseases that have high contribution to death among Malaysian. Hence, Malaysian is become aware about diabetes since many diabetes campaigns have been made by government in order to increase awareness among Malaysian. But then, diabetic people are having difficulties in order to decide what they should eat simply because they do not know the exact amount of total calories intake per day should they consume. Thus, this project develops a mobile application recommended system that assists diabetic people to decide what is the total calories intake per day should they consume based gender, age, body mass index, physical activity and diabetes stage. The target user of this mobile application is female with type-1 diabetic that age 31 until 50 years. This is because female is the most that suffered diabetes compared to male. The method that is being used for this mobile application is rule based expert system. Apart from that, since human is always uncertain with their decisions, certainty factor is integrated where this mobile application accepts user’s uncertain decision. Besides that, this mobile application can be enhanced in future works to get result that are more accurate. The criteria that user need to input can be added more so that the result will be more specific when the criteria is more detailed.